Mesenchymal Stem Cells Secretory Responses: Senescence Messaging Secretome and Immunomodulation Perspective - Lunyak, Victoria V.; Amaro-Ortiz, Alexandra; Gaur, Meenakshi (Frontiers in Genetics, 2017)
Mesenchymal stem/ stromal cells (MSC) have been tested in a significant number of clinical trials, where they exhibit regenerative and repair properties directly through their differentiation into the cells of the mesenchymal origin or by modulation of the tissue /organ microenvironment. Despite various clinical effects upon transplantation, the functional properties of these cells in natural settings and their role in tissue regeneration in vivo is not yet fully understood. The omnipresence of MSC throughout vascularized organs equates to a reservoir of potentially therapeutic regenerative depots throughout the body. However, these reservoirs could be subjected to cellular senescence. In this review, we will discuss current progress and challenges in the understanding of different biological pathways leading to senescence. We set out to highlight the seemingly paradoxical property of cellular senescence: its beneficial role in the development and tissue repair and detrimental impact of this process on tissue homeostasis in aging and disease. Taking into account the lessons from the different cell systems, this review elucidates how autocrine and paracrine properties of senescent MSC might impose an additional layer of complexity on the regulation of immune system in development and disease. New findings that have emerged in the last few years could shed light on sometimes seemingly controversial results obtained from MSC therapeutic applications.